A Review of Research on Russia’s Strategic Adjustment to the West under the Background of Russia-Ukraine Conflict - Qin, Yingyue (Transactions on Social Science, Education and Humanities Research, 2024)
This study aims to analyze Russia’s strategic adjustment to the West under the background of the Russia-Ukraine conflict, and to sort out and analyze the articles related to Russia’s strategic adjustment to the West in Chinese core journals and foreign journals from 2022 to 2024. This paper summarizes the views of domestic and foreign experts and scholars, and believes that since Russia took special military action against Ukraine, the United States and Europe have imposed unprecedented sanctions on Russia. In order to survive and develop the country and maintain its national status and interests, Russia has made a series of strategic adjustments in economy, science and technology, diplomacy and other fields, and made a strong response and counterattack to the Western sanctions policy. To some extent, it has effectively hedged the huge pressure brought by the sanctions, and showed the stability and resistance of Russia’s image as a major country to the international community.